Figure 1 from: Klass AL, Sokolova SE, Kondakov AV, Bespalaya YV, Gofarov MY, Tomilova AA, Vikhrev IV, Bolotov IN (2018) An example of a possible leech-bryozoan association in freshwater. ZooKeys 794: 23-30. https://doi.org/10.3897/zookeys.794.28088 - Klass, Anna L.; Sokolova, Svetlana E.; Kondakov, Alexander V.; Bespalaya, Yuliya V.; Gofarov, Mikhail Yu.; Tomilova, Alena A.; Vikhrev, Ilya V.; Bolotov, Ivan N. (Zenodo, 2018)
Figure 1 Map of Lena River basin, Eastern Siberia, with occurrence of the leech-bryozoan association in a floodplain lake (red dot).